Toward critical patriotism : student resistance to political education in Hong Kong and China - Fairbrother, Gregory P. (Hong Kong culture and society., 2003)
This book considers, in the context of political education in China and colonial Hong Kong, the effects of critical thinking on university students' attitudes toward the nation. Its objective is to understand how students' attitudes toward patriotism diverge from those held by the majority.